Dialog Agama dan Tantangan Teologi Global - Moh. Shofan (Budapest International Research and Critics University, 2014)
As we know, Frithjof Schuon, Seyyed Hossein Nasr, dan Fazlur Rahman have represented Islam pluralists in modern time, responding globalized world and international changes. This article reveal about the world view of the Islam pluralists who have struggled to exert pluralism. peace, solidarity, mutual understanding and respect for all of human beings. The Islamic path for peace, civilizational dialogue and mutual understanding is very significant for muslim and nonmuslim in building international peace, justice and solidarity.